2005
DOI: 10.1136/jnnp.2004.054882
|View full text |Cite
|
Sign up to set email alerts
|

A randomised phase II study of interleukin-1 receptor antagonist in acute stroke patients

Abstract: Objectives: The cytokine interleukin (IL)-1 mediates ischaemic brain damage in rodents. The endogenous, highly selective, IL-1 receptor antagonist (IL-1ra) protects against ischaemic cerebral injury in a range of experimental settings, and IL-1ra causes a marked reduction of cell death when administered peripherally or at a delay in transient cerebral ischaemia. We report here the first randomised, double blind, placebo controlled trial of recombinant human IL-1ra (rhIL-1ra) in patients with acute stroke. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
311
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 400 publications
(325 citation statements)
references
References 33 publications
7
311
0
4
Order By: Relevance
“…No adverse events were attributed to treatment and the recombinant human IL-1Ra was deemed safe. Ready transfer across the blood-brain barrier was shown [46]. Furthermore, systemic markers of biological activity (including neutrophil and total white cell counts, Creactive protein, and IL-6 concentrations) were lower in the treatment arm.…”
Section: Interleukin-1mentioning
confidence: 91%
See 1 more Smart Citation
“…No adverse events were attributed to treatment and the recombinant human IL-1Ra was deemed safe. Ready transfer across the blood-brain barrier was shown [46]. Furthermore, systemic markers of biological activity (including neutrophil and total white cell counts, Creactive protein, and IL-6 concentrations) were lower in the treatment arm.…”
Section: Interleukin-1mentioning
confidence: 91%
“…Clinical outcomes after at least 3 months were better in the treatment group. Median NIHSS score was reduced to 4 versus 1 in the placebo arm, and more patients receiving anakinra had mRS 0-1 at 3 months (30 % vs 7 %) [46].…”
Section: Interleukin-1mentioning
confidence: 92%
“…74 Animal studies demonstrated that a naturally occurring selective antagonist of the IL-1 receptor (IL-1ra) reduced stroke volume and disability when administered for up to 3 hours after onset of MCAO in rats. 72 Similarly, treatment with IL-1ra was initiated within 6 hours of stroke onset in stroke patients and was continued for 72 hours.…”
Section: Astrocytes Edema and Volume Regulation In Strokementioning
confidence: 99%
“…The IL-1 receptor antagonist (IL-1Ra) is a naturally occurring, competitive inhibitor of IL-1 action, which is highly selective. There is considerable preclinical and clinical evidence showing that IL-1Ra is a promising candidate for the treatment of stroke and related disorders (Banwell et al, 2009;Emsley et al, 2005;Hannum et al, 1990;Rothwell, 2003). In experimental stroke, endogenous IL-1Ra is upregulated and protects the brain (Denes et al, 2008;Pinteaux et al, 2006), while administration of exogenous IL-1Ra reduces ischemic injury, even when administered 3 hours after the insult (Garcia et al, 1995;Loddick and Rothwell, 1996;Mulcahy et al, 2003;Relton et al, 1996;Stroemer and Rothwell, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In experimental stroke, endogenous IL-1Ra is upregulated and protects the brain (Denes et al, 2008;Pinteaux et al, 2006), while administration of exogenous IL-1Ra reduces ischemic injury, even when administered 3 hours after the insult (Garcia et al, 1995;Loddick and Rothwell, 1996;Mulcahy et al, 2003;Relton et al, 1996;Stroemer and Rothwell, 1997). Subcutaneous IL-1Ra, administered at the time of occlusion, is neuroprotective in the rat and localizes to salvageable brain tissue (Greenhalgh et al, 2010), and IL-1Ra showed some beneficial effects in a small phase II clinical study in acute stroke (Emsley et al, 2005).…”
Section: Introductionmentioning
confidence: 99%